"When I get older, I wanna be an entrepreneur": the impact of disability and dyslexia on entrepreneurial self-efficacy perception. Issue 2 (11th December 2020) - Powers, Benjamin; Le Loarne-Lemaire, Séverine; Maalaoui, Adnane; Kraus, Sascha
Abstract : Purpose: This article contributes to the literature on entrepreneurship for people with disabilities through a better understanding of the impact of entrepreneurial self-efficacy perceptions on entrepreneurial intentions in populations with lower levels of self-esteem. It investigates the entrepreneurial intention and self-efficacy of a population of students suffering from dyslexia, which is a learning disability. Design/methodology/approach: The paper is based on the study of a data set of 796 male and female adolescents in the USA, aged 13–19 years, both with and without dyslexia. The sample is a convenient one. The whole sample replied to the questionnaire on their self-efficacy perception and their intention to create, one day, their own venture. They also self-declare their dyslexia. Regressions have been conducted to answer the research question. Findings: Results show that having dyslexia has a negative impact on entrepreneurial self-efficacy perceptions. They also reveal that self-efficacy perceptions mediate the relationship between dyslexia and entrepreneurial intentions and their three antecedents (social norms, control behavior and perceived ability). Research limitations/implications: The sample is composed of students from private schools and might socially be biased. Practical implications: Our findings relaunch the debate on the necessity to develop education programs that consider the personal-level variables of students, specifically the development of entrepreneurial self-efficacy among adolescents with disabilities Social implications: Such findings should help to better understand students who are suffering from dyslexia and help them find a place in society and economic life. Originality/value: This is so far the first study that has been conducted on dyslexic adolescents.